Photocatalytic degradation of methylene blue by C3N4/ZnO: The effect of the melamine/ZnO ratios - Pongsaton Amornpitoksuk (2018)
© Indian Academy of Sciences. The C3N4/ZnO composite photocatalysts were synthesized by mechanical milling combined with a calcination process. Various ratios of melamine and ZnO powders were milled by a planetary ball mill for 10 h. After heating at 540?C for 3 h in air, melamine was converted to C3N4 but the formation of C3N4 depended on the ratios of the melamine and ZnO (M/Z) powders. From the experimental results, the conversion of melamine to C3N4 could be inhibited by ZnO particles; as there was no detectable C3N4 in the sample at low M/Z values or high ZnO contents. The photocatalytic activities of prepared samples were investigated under the illumination of blacklight and fluorescent lamps as the low wattage light source. The C3N4/ZnO showed a better photocatalytic activity than ZnO to degrade a methylene blue (MB) dye solution using blacklight lamps, but there is no significant difference in photocatalytic activities between ZnO and prepared C3N4/ZnO under visible light by the fluorescent lamps. However, the prepared C3N4/ZnO can well function under illumination by Xe lamp as the high power light source. Ecotoxicities of MB solutions before and after photocatalytic process were also studied through growth inhibition of the alga Chlorella vulgaris.